A Label-Free Immunosensor Based on Gold Nanoparticles/Thionine for Sensitive Detection of PAT Protein in Genetically Modified Crops - Yang, Qianwen; Wang, Yu; Liu, Xiaofeng; Liu, Hua; Bao, Huifang; Wang, Jinbin; Zeng, Haijuan (Frontiers in Chemistry, 2021)
Genetically modified (GM) crops containing phosphinothricin acetyltransferase (PAT) protein has been widely planted worldwide. The development of a rapid method for detecting PAT protein is of great importance to food supervision. In this study, a simple label-free electrochemical immunosensor for the ultrasensitive detection of PAT protein was constructed using thionine (Thi)/gold nanoparticles (AuNPs) as signal amplification molecules and electrochemically active substances. Under optimum conditions, the limits of detection of the sensor for soybean A2704-12 and maize BT-176 were 0.02% and 0.03%, respectively. The sensor could detect crops containing PAT protein and had no cross-reaction with other proteins. After storage at 4°C for 33 d, the sensor still retained 82.5% of the original signal, with a relative standard deviation (RSD) of 0.92%. The recoveries of the sensor for soybean A2704-12 and maize BT-176 were 85%–108% and 98%–113%, respectively. The developed PAT-target immunosensor with high sensitivity, specificity, and satisfactory reproducibility and accuracy will be a useful tool in the trace screening of GM crops. Moreover, this design concept can be extended to other proteins by simply changing the antibody.